Looking for Alternative Online Promotion Strategy in Virtual Store-front Through Analytic Hierarchy Process - Abdillah, F; Kusnad, K (Proceeding Interuniversity Forum for Strengthening Academic Competency, 2019)
Technology, especially the Internet, keeps growing nowadays to offer a more convenience living. Exchanging information via Internet becomes easier and limitless. Consequently, it has been used to advance business and brings alternative promotion strategies. Previous researches in e-business less specifically concerned to promotional strategy, so that the current study aimed at exploring the implementation of analytic hierarchy process (AHP) in a virtual store-front and finding elements that support the online promotion strategy. Data in this research was gathered by the qualitative and quantitative approach. The results showed that the implementation of online promotion strategy by the company consists of web promotion with the CPC system, price discount, social networking systems, smartphone application, and group discussion. Meanwhile, the actors who involve in strategic decision making included the director, marketing manager, and IT Department. The company has been developing an online marketing strategy to increase sales, consumers’ awareness, competitive advantage, and dissemination of information. The alternative strategies that could support the company's strategic actions, based on the rank order of priority, are the marketplace, search engine optimization, webvertising, and direct mail. Further, technical application for online business industries could give priority to IT skill development.